INFLUENCE OF SOCIAL MEDIA ADVERTISING ON BRANDS AWARENESS OF PT. INDAH TAMARA TOUR & TRAVEL CUSTOMERS - shanti oktavia Putri; Angel Purwanti (Jurnal Apresiasi Ekonomi, 2018)
One of the strategies use of the company in products introducing and services is by advertising. advertising media so many using now that is social media or marketing Social Media. One of the travel company used social media as advertising media is PT Indah Tamara Tour & Travel. In except to advertising strategy the company also needs to develop Brand Awareness will be the company's brand for its products familliar among consumers. The purpose of this research is to determine of the effect of advertising on brand awareness of consumers and the influence of social media on the relationship between Advertising with Brand awareness consumers. Sampling technique in this research use Simple Random sampling method. Data collection techniques use in this research was by means of questionnaires. The result of hypothesis 1, t test (13,347) ˃ t table (1,966) with significance value 0,000